Macropsychanthus nitidus: a new rank and combination for dioclea rostrata var. nitida (leguminosae, papilionoideae) - Fonseca-Cortés, Andrés; Snak, Cristiane; Queiroz, Luciano Paganucci De (Phytotaxa, 2023)
As a part of the studies in Neotropical Macropsychanthus, we propose a new rank and combination for Dioclea rostrata var. nitida: Macropsychantbus nitidus. This species is unique in the genus by the combination of leaf rachis to 2 cm long, leaflet undersurface sericeous argenteus and keel apex straight. Although this species was included as a variety of Dioclea rostrata or as a synonym of Macropsychanthus bicolor, we discuss why it should be recognized as a different species. A detailed taxonomic description, distribution map, illustration, and a discussion with similar taxa are provided.